If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = -4x + 3x Multiply F * x xF = -4x + 3x Combine like terms: -4x + 3x = -1x xF = -1x Solving xF = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. x + xF = -1x + x Combine like terms: -1x + x = 0 x + xF = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(1 + F) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + F)' equal to zero and attempt to solve: Simplifying 1 + F = 0 Solving 1 + F = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + F = 0 + -1 Combine like terms: 1 + -1 = 0 0 + F = 0 + -1 F = 0 + -1 Combine like terms: 0 + -1 = -1 F = -1 Add '-1F' to each side of the equation. F + -1F = -1 + -1F Combine like terms: F + -1F = 0 0 = -1 + -1F Simplifying 0 = -1 + -1F The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| -18=2v | | 72-x+3=15 | | 3x-(4)=0 | | 0.93x^2+2.2x+130=164 | | 2(2-4a)+18=6 | | 5(2r-7)=9 | | v^2=18v-23 | | (12/73)(5/8) | | 6b+10=18 | | 2(b+2)-(6+b)=-5 | | 25=3(2a+1)+5 | | 9=3/4y | | .09=3/4y | | 2.2*4a+5=1.8a-3 | | 1.025x^2-4x+20=-2.125x^2+6x+40 | | (5y+7)-(2+4y)=8 | | 15-5k=20 | | (5y+7)-(5-4y)=9 | | (-12m^10)/(3m^3) | | 9x^2+7y^2+18x-28y-26=0 | | 6x^3-6x^2-4x+8=0 | | 7(x-6)+13=2(x-7) | | (5x^4+6x^3-7)-(9x^2-4x+2)= | | 3056899999-15000000x=3000000000 | | x^2-10x-400=386 | | x*1.96=42.80 | | 2x(4x-3)-5(4x-3)=0 | | -5x+3=-2(4x+12) | | f(x)=-3x^2+6x-7 | | (X-2)(x+4)=y | | 3d=3d+9 | | 12w-4= |